The Role of Emotional Marketing and Destination Image on Positive Electronic Word of Mouth through Tourist Satisfaction as a Mediating Variable in Siantar Zoo Tourism - Riki Riduansyah Rambe; Endang Sulistya Rini; Syafrizal Helmi Situmorang (International Journal of Economics, Commerce, and Management, 2025)
This research uses visitor satisfaction as a mediating variable to examine and ascertain how emotional marketing and destination image affect positive electronic word-of-mouth in relation to Siantar Zoo tourism. Tourists who have been to Siantar Zoo made up the study's population. There are 271 responders in the sample utilized in this investigation. A questionnaire survey is the method used in this research to gather data. Descriptive analysis and the Structural Equation Model (PLS) were used in the data analysis process. Smart-PLS version 4 was utilized for data processing in the research. According to the study's findings, tourist satisfaction was positively but marginally impacted by emotional marketing. Tourist satisfaction was positively and significantly impacted by destination image. Positive Electronic Word of Mouth was significantly and favorably impacted by emotional marketing. Positive Electronic Word of Mouth is significantly and favorably impacted by destination image. Positive Electronic Word of Mouth is positively and significantly impacted by visitor satisfaction. Positive Electronic Word of Mouth via Visitor Satisfaction is not much impacted by emotional marketing. Through visitor satisfaction, destination image significantly influences positive electronic word-of-mouth. Determination Coefficient studies show that destination image, emotional marketing, and visitor satisfaction account for 56% of positive electronic word-of-mouth.